Method for locally regulating regenerated sodium-based cathode material based on waste electrode sheet and application

CN122977459APending Publication Date: 2026-10-27WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611167343.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服上述技术不足,提供一种基于废旧电极片局域调控再生钠基正极材料及方法和应用,解决现有技术中难以有效识别和调控电极材料普遍存在的局域非均匀反应导致提前失效的技术问题

Benefits of technology

[0009]与现有技术相比,本发明的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977459A_ABST
    Figure CN122977459A_ABST
Patent Text Reader

Abstract

The application relates to a kind of based on waste electrode piece local area regulation and control regenerated sodium-based positive electrode material and method and application, comprising the following steps: waste electrode piece is immersed in water-based solvent, waste positive electrode material is stripped and continues to soak, and sodium removal strain treatment is carried out;Afterwards, material A is obtained by solid-liquid separation and drying;Material A is immersed in salt solution containing target doping element to obtain material B;Sodium salt is added to material B to carry out sodium supplement treatment, and mixed powder C is obtained;Sodium-based positive electrode material is obtained by sintering mixed powder C.The application guides heterogeneous strain in the heterogeneous phase region by regulating and controlling sodium removal stress, produces crack at fixed point, provides identification basis for subsequent local accurate modification;Afterwards, target element is carried into crack position by solution, realizes local attachment of target element in heterogeneous reaction area;Finally, element doping is realized by sodium supplement regeneration simultaneously, and target product is obtained.The application is novel in route, simple in process, and can realize effective identification and regulation of local heterogeneous reaction of electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery materials, specifically to a method and application of locally controlled regenerated sodium-based cathode materials based on waste electrode sheets. Background Technology

[0002] Non-uniform reactions have long been a key factor limiting the performance of electrode materials. Influenced by complex factors such as structural defects, crystal orientation, and particle size, battery materials generally face the challenge of non-uniform reactions. Nat. Commun. 2023, 14: 8394), leading to preferential failure of materials in localized areas in practical applications, resulting in overall performance degradation. Adv. Mater. 2025, 37: 2419253). Although the effects of nonhomogeneous reactions have been extensively investigated, the complex inducing factors have made it difficult to effectively locate and resolve them.

[0003] In previous studies, heteroelement doping has been an important means of strengthening crystal structures. However, traditional surface or bulk doping often results in the overall replacement of the modified regional structure. On the one hand, it easily falls into a "capacity-stability" balance dilemma; on the other hand, overall control cannot change the "barrel effect" problem of weak local areas in the overall structure, which leads to the problem of preferential failure of non-uniform reaction localities under long-term cycling. In recent years, researchers have begun to focus on the study of local structure control. For example, Professor Peng Bo of Anhui University of Technology, in collaboration with Professor Zhou Haoshen of Nanjing University, proposed a grain boundary welding control technology (…). Adv. Mater. 2025, 38: e14943). The aim is to eliminate the local "weakest link" effect by reducing grain boundaries where side reactions are severe. However, grain boundaries are only one region where inhomogeneous reactions are concentrated, and solutions to the inhomogeneous reaction problem at non-grain boundaries remain elusive.

[0004] Although researchers have fully recognized the complexity and harmfulness of nonuniform reactions in previous studies, the causes of nonuniform reactions are complex and randomly distributed, making them difficult to identify and locate in conventional methods, thus lacking effective countermeasures. Summary of the Invention

[0005] The purpose of this invention is to overcome the above-mentioned technical deficiencies and provide a method and application for the localized regulation of regenerated sodium-based cathode materials based on waste electrode sheets, thereby solving the technical problem in the prior art that it is difficult to effectively identify and regulate the localized non-uniform reaction that is common in electrode materials, leading to premature failure.

[0006] To achieve the above-mentioned technical objectives, the technical solution provided by this invention is as follows: In a first aspect, the present invention provides a method for regenerating sodium-based cathode materials based on localized regulation of waste electrode sheets, comprising the following steps: S1, immersing the waste electrode sheets in an aqueous solvent, peeling off the waste cathode material and continuing to immerse, and performing sodium removal strain treatment; subsequently, after solid-liquid separation and drying, material A is obtained; S2, immersing material A in a salt solution containing the target dopant element, to obtain material B; S3, adding sodium salt to material B for sodium replenishment treatment, to obtain mixed powder C; and sintering the mixed powder C to obtain sodium-based cathode materials.

[0007] Secondly, the present invention provides a sodium-based cathode material regenerated by the above method.

[0008] Thirdly, the present invention provides an application of the above-mentioned sodium-based cathode material in the preparation of sodium-ion batteries.

[0009] Compared with the prior art, the beneficial effects of the present invention include: This invention first treats waste electrode sheets by immersing them in an aqueous solvent. The waste cathode material is then detached from the current collector and further immersed in the solvent. By controlling the sodium removal (H / Na exchange) stress, non-uniform strain in the heterogeneous region is guided, inducing cracks at specific points. This selectively exposes the region, providing a basis for subsequent precise local modification. Next, depending on the modification objective, the material is immersed in different salt solutions. The solution carries the target element to the crack location, achieving local attachment of the target element in the non-uniform reaction region. Finally, a unified sodium replenishment regeneration process simultaneously enhances the elemental doping, yielding the target product. This invention is a method for localized control of sodium-based cathode materials based on non-uniform strain. It features a novel approach and simple process, effectively identifying and controlling the ubiquitous localized non-uniform reactions in electrode materials. This provides technical support for the precise local structural strengthening of sodium-based oxide materials to suppress premature failure. Attached Figure Description

[0010] Figure 1 The images show the high-magnification and low-magnification SEM morphologies of material A obtained after sodium removal strain treatment in 50W solvent in Example 1 of this invention. Figure 2 The bulk phase distribution morphology of cracks in material A obtained by immersion treatment with 50W solvent in Example 1 of this invention; Figure 3 This is a crack distribution diagram of the bulk phase A of the material obtained by immersion treatment in 50W solvent in Example 1 of the present invention. Figure 4 The heterogeneous structure characteristics at the crack of material A obtained by immersion treatment with 50W solvent in Example 1 of this invention; Figure 5 The SEM morphology of the target product 50W-20 material obtained by regeneration in Example 1 of this invention is shown at high and low magnification. Figure 6The images show SEM images of crack distribution in the materials treated with 100W and 25W solvents in Examples 2-3 of this invention; where (a) is the immersion treatment with 100W solvent in Example 2, and (b) is the immersion treatment with 25W solvent in Example 3. Figure 7 The XRD patterns of the regenerated materials after treatment with different solvents in Examples 2-3 of this invention are shown below. Figure 8 The image shows the SEM morphology of the 50W-0 material obtained in Comparative Example 1 of this invention without dopant. Figure 9 The images are aberration-corrected electron microscope images of W-doped materials obtained in Comparative Example 2 (conventional 50W@10) and Example 4 of the present invention (50W-10); where (a) is Comparative Example 2 and (b) is Example 4. Figure 10 The first-cycle charge-discharge curves and long-cycle performance of the sodium-based cathode materials obtained in Example 1 and Comparative Example 1 of this invention are compared; where (a) is the first-cycle charge-discharge curve and (b) is the cycle performance. Figure 11 The first-week charge-discharge curves of the recycled materials after different solvent treatments in Examples 1-3 and Comparative Example 1 of this invention are shown. Figure 12 The first-cycle charge-discharge and cycling performance of the conventional and locally oriented doped W materials in Comparative Example 2 of this invention are shown. Detailed Implementation

[0011] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0012] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the invention; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the invention, are intended to cover non-exclusive inclusion.

[0013] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of the invention. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0014] In previous research, the applicant noted that waste sodium-based oxide materials undergo desodiumification upon contact with water, leading to inhomogeneous slippage of the crystal structure and the generation of macroscopic cracks. Essentially, the intrinsic heterogeneous structure of waste materials is spontaneously formed under long-term inhomogeneous reactions. Therefore, theoretically, by rationally inducing preferential strain in the intrinsic heterogeneous structure of waste materials, it is possible to inversely identify the inhomogeneous reaction region.

[0015] Based on this, in order to solve the problem of premature failure caused by the prevalent local non-uniform reaction in traditional electrode materials, which is difficult to effectively identify and control, this invention was established.

[0016] Unlike traditional research that focuses on modifying the structure of finished materials, this application reversely identifies non-uniform reaction zones from waste materials; it utilizes the non-uniform strain of the intrinsic heterogeneous structure of waste materials to induce precise local exposure; and then, based on the precise local control of the non-uniform reaction zones, it eliminates the intrinsic non-uniform reaction of the materials.

[0017] In a first aspect, the present invention provides a method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets, comprising the following steps: S1, the waste electrode sheet is immersed in an aqueous solvent to peel off the waste positive electrode material and continue to soak it for sodium removal strain treatment; then, after solid-liquid separation and drying, material A is obtained; S2, Immerse material A in a salt solution containing the target dopant element to promote the fixed-site adhesion of the element and obtain material B; S3, sodium salt is added to material B for sodium supplementation treatment to obtain mixed powder C; mixed powder C is sintered to obtain a sodium-based cathode material with localized doping enhancement.

[0018] This invention first treats waste electrode sheets by immersing them in an aqueous solvent to remove the waste cathode material from the current collector. The cathode material is then further immersed in the aqueous solvent for sodium removal strain treatment (H / Na exchange), guiding non-uniform strain in the heterogeneous region and generating cracks, thereby selectively exposing this area. This invention creates cracks at specific points (controllable sodium removal strain treatment is the core of crack creation), providing an identification basis for subsequent precise local modification. Then, depending on the modification purpose, the material is immersed in different salt solutions, and the target element is carried to the crack location via a liquid-phase method using solution diffusion characteristics, achieving point-to-point adsorption of elements in the non-uniform reaction region. Finally, a unified sodium replenishment regeneration process is performed, and high-temperature sintering simultaneously achieves local doping of the target element, yielding the target product. This invention is a method for localized control of sodium-based cathode materials based on non-uniform strain. This method features a novel approach and simple process, enabling effective identification and control of the localized non-uniform reactions commonly found in electrode materials, providing technical support for the precise strengthening of the local structure of sodium-based oxide materials to suppress premature failure.

[0019] In some embodiments, in step S1, the waste electrode sheets are from Ah-level pouch cells that have experienced long-cycle failures at sodium battery companies.

[0020] In some embodiments, in step S1, the chemical formula of the waste cathode material is Na. x Ni y Mn z Me w O2 and Me are selected from at least one of Fe, Mg, Al, Cu, Co, Sn, Ti and Zn, wherein 0≤x≤1, 0≤y≤0.5, 0.3≤z≤1.0, 0≤w≤0.4, and y+z+w=1. The waste cathode material of this invention can be in any state (single crystal, polycrystalline, charged state, discharged state, etc.).

[0021] In some embodiments, in step S1, the water-based solvent includes water or a mixture of water and a small molecule polar organic reagent, wherein the small molecule polar organic reagent includes one or more of methanol, ethanol, propanol, acetone, urea, and dimethyl sulfoxide.

[0022] Preferably, when the water-based solvent is a mixture, the mixing volume ratio of water to the small-molecule polar organic reagent is 1:(0.01-3), more preferably 1:(0.5-2), and even more preferably 1:1. This invention balances solvent diffusion and desodium strain by controlling the mixing volume ratio of water to the small-molecule polar organic reagent.

[0023] In some embodiments, in step S1, the soaking time for peeling off the waste positive electrode material is 0-10 min, and the sodium removal strain treatment is performed under ultrasonic conditions for 10-60 min. In this invention, immersing the waste electrode sheet in a water-based solvent can be divided into two steps: a short initial treatment to peel off the waste positive electrode material, and a relatively longer soaking time for a second soaking treatment to achieve targeted cracking through sodium removal strain.

[0024] In some embodiments, in step S2, the salt solution containing the target dopant element includes at least one of Li, Cu, W, and Ca, and the salt includes a sodium salt, chloride salt, acetate, or nitrate salt. The solvent is the same as the water-based solvent in step S1. The solvent in the salt solution of this invention is consistent with the water-based solvent, mainly by disrupting the hydrogen bond network of water to increase the solution permeation rate and reduce the H / Na exchange rate, while also maintaining the concentration of the salt solution.

[0025] It is understood that the target doping elements specified above are only common types, and those skilled in the art can choose other types according to actual needs without having to overcome difficulties.

[0026] In some embodiments, in step S2, the concentration of the salt solution containing the target dopant element is 0.1 mmol / L to a saturation concentration.

[0027] In some embodiments, step S2 specifically includes: immersing material A in a salt solution containing the target dopant element, first sonicating for 10–60 min, then soaking for 5–24 h to obtain material B. This invention achieves localized adsorption through immersion, and the ultrasonic treatment during this process promotes the penetration of the salt solution into the pores, achieving precise localized attachment of the target element.

[0028] In some embodiments, in step S3, the sodium salt includes at least one active sodium selected from Na2CO3, NaOH, NaNO3, and Na2O; wherein, active sodium is preferred over inert sodium such as sodium chloride and sodium sulfate, which contain sodium ions but cannot intercalate sodium; the amount of sodium salt added in the sodium replenishment process is calculated based on the theoretical molar amount of the target product, which can be calculated based on the constant areal density of the commercial electrode sheet, thereby accurately measuring the amount of sodium salt to be replenished.

[0029] In some embodiments, in step S3, the sintering temperature is 600–1200°C and the sintering time is 1–20 h.

[0030] Secondly, the present invention provides a sodium-based cathode material regenerated by the above method.

[0031] Thirdly, the present invention provides an application of the above-mentioned sodium-based cathode material in the preparation of sodium-ion batteries.

[0032] The main mechanism of this invention lies in its use of the intrinsic heterogeneous structure of waste materials (the coexistence of the original layered phase and the spinel / rock salt phase after phase transformation) as a starting point. It utilizes the differentiated strain characteristics of the heterogeneous structure upon contact with water (layered phases undergo interlayer slippage during sodium removal upon contact with water, while the rock salt or spinel phase remains stable) to precisely expose the non-uniform reaction zone. In the waste material treatment stage (step S1), the composition of the water-based solvent is controlled to achieve a balance between the sodium removal stress and the solvent diffusion rate into the particles. Subsequently, in step S2, a salt solution containing the target dopant element is introduced into the strained region through liquid-phase permeation, enabling precise delivery of the target element. Ultimately, the cathode material obtained by this invention differs from conventional doping; it achieves precise modification and enhancement of weak micro-regions in the non-uniform reaction, avoiding the problem of premature overall failure caused by localized degradation.

[0033] Specifically, the main advantages of this invention include: (1) Regarding the identification of non-uniform reaction sites, unlike previous methods that struggled to effectively distinguish finished materials, this invention employs a reverse approach. It utilizes the heterogeneous structural characteristics formed by spontaneous non-uniform reactions during long-term recycling of waste materials, leveraging strain differences in the heterogeneous structure to actively expose the non-uniform reaction zone. Simultaneously, it considers that besides significant stress between heterogeneous phases, strain differences between the outer desodium-free zone and the inner non-desodium-free zone due to diffusion rate differences can also lead to cracks, thus interfering with the exposure of the heterogeneous interface. Therefore, this invention consciously controls the water ratio in the water-based solvent. Excessive water leads to excessively rapid desodium removal, while increasing polar solvents such as ethanol helps break the hydrogen bond network of water, thereby increasing the solution diffusion rate and reducing the H / Na exchange rate. This is a crucial control condition in the identification of non-uniform reaction sites.

[0034] (2) Introducing dopant elements into the strain crack interface facilitates precise local modification, achieving precise enhancement of weak local areas by the dopant elements. Common pathways for controlling the surface of bulk microcracks include gas-phase diffusion or liquid-phase infiltration. This invention achieves precise local attachment of target elements through solution infiltration. The amount of salt doping is achieved by controlling the salt concentration or based on chemical reactions. In the subsequent sodium-added sintering, the dopant elements remaining on the surface will simultaneously participate in the reconstruction of the local structure.

[0035] The present invention will be further described in detail below through specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions. Reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0036] Before processing, the waste electrode sheets can be cut to an appropriate size to facilitate processing in beakers or corresponding instruments. The molar amount of waste positive electrode material in the waste electrode sheets is calculated based on the electrode surface load multiplied by the area, and its chemical formula is NaNi. 1 / 3 Mn 1 / 3 Fe 1 / 3 O2.

[0037] Example 1 A method for locally controlling the regenerated sodium-based cathode based on waste materials includes the following steps: S1. First, immerse the waste electrode sheet in 30 mL of water-based solvent (V 水 V 乙醇 =1:1; 50W), wait for the active material to detach from the aluminum foil (<1min), then remove the aluminum foil. The remaining active material is sonicated in a 50W water-based solvent for 30min, filtered, and dried to obtain material A.

[0038] S2, prepare a 20 mmol / L sodium tungstate solution in 50W solvent; take 2 mmol (calculated based on the actual loading of commercial materials) of the treated material A and immerse it in 5 mL of the sodium tungstate solution, sonicate for 30 min and soak overnight (12 h), and introduce W element into the crack interface by solution permeation; filter and separate the material, wash it three times with ethanol and water alternately to remove the W salt attached to the surface, and dry to obtain material B.

[0039] S3, add 1 mmol of sodium carbonate to material B according to the stoichiometric ratio, and sinter the material by first heating it to 450℃ at a rate of 3℃ / min and holding it for 5h, and then heating it to 850℃ at a rate of 5℃ / min and holding it for 18h to obtain the sodium-based cathode material, denoted as 50W-20.

[0040] The regeneration process of this invention involves targeted doping at the crack interface W, thereby achieving localized directional strengthening of the non-uniform reaction zone. The following is a characterization process using specific morphological tests.

[0041] First, material A obtained from the sodium removal strain treatment undergoes strain under non-uniform sodium removal stress, and its morphology is as follows: Figure 1 As shown, the particles exhibit interlaminar cracks. Further analysis using cross-sectional methods... Figure 2 The observation of crack diffusion from the surface to the bulk phase within the particles demonstrates the localized selective strain characteristics under 50W solution treatment. Simultaneously, the strain cracks propagate into the bulk phase as the solvent penetrates, indicating the influence of solvent selection on the strain region.

[0042] In this invention, the active exposure of the heterogeneous reaction zone utilizes the spontaneously formed heterogeneous transformation characteristics of the "layered-spinel / rock salt phase" during material cycling. The layered phase readily undergoes desodiumation and interlayer slip when exposed to water, while the spinel / rock salt phase remains unchanged due to its inertness, resulting in interphase crystal plane dislocation and crack formation at the heterogeneous interface. This invention achieves full exposure of the heterogeneous region by controlling the solvent composition and balancing the desodiumation rate to control the strain stress of the layered phase and the solvent diffusion rate in the pores. The structure of material A slice treated with 50W solvent is shown below. Figure 3 As shown, the distribution of cracks of varying sizes across the entire cross-section indicates uneven stress and strain during solvent immersion, which is related to the non-uniform phase distribution of the material itself.

[0043] To further illustrate the correlation between crack initiation and heterogeneous structure, the following was conducted: Figure 3 Further magnification of the structural features of the medium crack revealed the following results: Figure 4As shown, four locations were selected on both the upper and lower sides of the crack for observation. Region I on the upper side of the crack maintained a good layered structure, while the lower side showed a transitional structure of layered slip, indicating that the crack initiation is related to the heterogeneous structure on both sides of the crack. Further observation of the crystal plane characteristics of the crack region revealed that regions III and IV demonstrated the transitional characteristics of the structure during the crack initiation process. The crack interface exhibited a disordered structure, which can be attributed to structural dislocation and subsequent cracking at the heterogeneous interface under stress and strain as stress is generated.

[0044] Based on the above, it has been demonstrated that the present invention can induce stress and strain preferentially and generate cracks in heterogeneous structural regions through solvent regulation, thereby providing an exposure environment for the subsequent directional strengthening of heterogeneous regions.

[0045] After subsequent sodium replenishment and regeneration, the resulting 50W-20 material was regrowed into a dense bulk structure. Figure 5 Compared to the significant cracking characteristics after solvent immersion treatment () Figure 1 The reconstructed structure successfully regenerated.

[0046] Example 2 Compared with Example 1, the only difference is that the water-based solvent in step S1 is 100% water (100W); the other steps and conditions are the same as in Example 1, and the resulting sodium-based cathode material is denoted as 100W-20.

[0047] Example 3 Compared with Example 1, the only difference is that the water-based solvent in step S1 is a mixture of 25% water and 75% ethanol (25W); the other steps and conditions are the same as in Example 1, and the resulting sodium-based cathode material is denoted as 25W-20.

[0048] The results showed that when the water ratio was too high, the sodium removal rate was too fast, and surface-dominated strain was prone to occur. In this case, the 100W solvent diffusion was not timely, and the resulting stress-strain was influenced to some extent by the "bulk-surface" gradient strain, resulting in insufficient exposure of the bulk heterogeneous region (cracks) compared to Example 1. Figure 6 However, the purpose of this invention can still be achieved. In contrast, when the water ratio is low (25W), the cracks are fine and not significant, indicating that the 25W solvent has sufficient diffusion and insufficient desodium stress.

[0049] Figure 7XRD analysis showed that the layered phase structure of several types of materials was well restored after regeneration. However, due to the insignificant cracks in the 25W-treated sample and the insufficient sodium intercalation process, some rock salt phase impurities were observed in the XRD spectrum. The reintercalation process depends on sufficient exposure of the specific surface area to promote ion diffusion. Because the 25W sample had insufficient specific surface area exposure, it was not completely repaired during the regeneration process. Therefore, the water-based solvent in this invention includes water or a mixture of water and a small-molecule polar organic reagent in a volume ratio of 1:(0.01–3), more preferably a mixture of 1:(0.5–2), and even more preferably a mixture of 1:1.

[0050] Example 4 Compared with Example 1, the only difference is that the W salt concentration is reduced to 10 mmol / L; the other steps and conditions are the same as in Example 1, and the resulting sodium-based cathode material is denoted as 50W-10.

[0051] Since the W doping amount is mainly determined by the W salt content adsorbed on the exposed surface of the material after solution immersion, the salt concentration is key to controlling the doping amount. The W doping amount of the regenerated materials from Examples 1 and 4 was compared using ICP-OES. Due to the low solution concentration, the W content in the 50W-10 sample was approximately 0.10. mol ‰, only slightly lower than 0.13 for 50W-20. mol Therefore, the subsequent electrochemical data for both are quite similar, with 50W-10 exhibiting a slightly higher reversible specific capacity. Nevertheless, this invention chose W as the dopant not only to demonstrate the positive effect of doping but also because W, with its high atomic number, exhibits segregation characteristics during doping, making it easier to observe the dopant element's position and signal intensity in subsequent studies. In fact, although the W doping amount here is low, under normal conditions this content is sufficient to induce a phase transition in the material structure.

[0052] Example 5 Compared to Example 1, the only difference is that the waste electrode sheets were sourced from retired sodium-based oxide cells provided by different partner companies. The different sources of waste materials demonstrate that induced strain has universal applicability to materials prone to H / Na exchange. Meanwhile, the dopant was replaced with Cu salt instead of W salt, the copper nitrate solution concentration was 50 mmol / L, and other steps and conditions were the same as in Example 1. The resulting material is denoted as 50W-50Cu.

[0053] Compared to W, which is prone to segregation, Cu, as a dopant, exhibits better diffusivity. Therefore, by selecting two typical segregation-type and diffusion-type dopants, W and Cu, this study compares them with traditional surface or bulk doping to demonstrate the unique advantages of directional doping.

[0054] Comparative Example 1 The only difference from Example 1 is that step S2 is removed, while the other steps and conditions are the same as in Example 1, resulting in a sodium-based cathode material without localized W doping, denoted as 50W-0.

[0055] Without introducing dopants, Comparative Example 1 yielded only conventional material (50W-0), which served as a control group to verify the modification effects of doping and directional doping.

[0056] The morphology of the 50W-0 material obtained in Comparative Example 1 without dopant is as follows: Figure 8 As shown, the dense, bulk-like particles indicate that doping does not change the material morphology, and the difference in performance is only related to the introduction of heterogeneous elements to regulate the structure.

[0057] Comparative Example 2 Compared with Example 4, the only difference is that the W dopant is added by a solid-phase method instead of a liquid-phase method, that is, an equimolar amount of solid sodium tungstate is directly added and sodium is added simultaneously for sintering. The other steps and conditions are the same as in Example 4, and the resulting material is denoted as 50W@10.

[0058] According to the ICP-OES results, the dopant in Comparative Example 2 mainly exhibits surface doping rather than the localized directional doping proposed in this invention, which helps to demonstrate the advanced nature of directional doping.

[0059] Figure 9 Aberration-corrected electron microscopy (SEM) atomic arrangements of the materials after surface and localized directional doping are presented. Under conventional doping, the typical layered structure within a 6 nm thickness of the surface completely transforms into a rock-salt-like phase structure, a structural change that easily leads to poor ion transport. In contrast, although an equal amount of W is introduced, the W distribution in localized directional doping differs from the non-uniform reaction region in the bulk phase, and is only effective for the localized structure. Therefore, directional doping avoids unfavorable structural transformations, and its surface layered structure remains intact.

[0060] Therefore, as can be seen from Example 4 and Comparative Example 2, W with equal amounts of conventional doping tends to segregate on the particle surface, causing the material surface structure to completely transform from a layered phase to a rock salt phase; while this phenomenon was not found in the directionally doped 50W-10 sample (obtained in Example 4), highlighting the special effect of localized directional doping.

[0061] Comparative Example 3 Compared with Example 5, the only difference is that solid copper nitrate is added and sintered simultaneously according to the molar amount of Cu doped with 50W-50Cu. Other steps and conditions are the same as in Example 5, and the resulting material is denoted as 50W@50.

[0062] Unlike W, which exhibits segregation characteristics, Cu, with its diffusion properties, is widely used in sodium-based layered oxides and shows good optimization effects. This example further illustrates that even when conventional modifications are beneficial for improvement, localized directional doping still offers performance advantages. Thus, the universal applicability of localized directional doping is verified in both segregation-type and diffusion-type doping cases.

[0063] Application Example 1 The application of a sodium-based cathode material in the preparation of sodium-ion batteries includes the following specific steps: The regenerated sodium-based cathode material was mixed with conductive carbon black (conductive agent) and polyvinylidene fluoride (PVDF binder) at a mass ratio of 8:1:1. A small amount of N-methylpyrrolidone (NMP) was added and the mixture was ground and thoroughly mixed to form a uniform slurry. This slurry was coated onto an aluminum foil substrate as a test electrode. The electrolyte was 1M NaClO4 / PC:EMC (V:V = 50:45) + 5% FEC. A coin cell was fabricated using a sodium metal sheet as the counter electrode.

[0064] Constant current charge-discharge performance tests were conducted on coin cells assembled using the sodium-based cathode materials obtained in Examples 1-5 and Comparative Examples 1-3, respectively. The test temperature was kept constant at 25°C, the current density for the first cycle was 0.1C, followed by long-term cycling at 1C (130 mA / g); the voltage range was 2.0–4.1V. The results are shown in Table 1 and [Table data missing]. Figures 10-12 As shown.

[0065] Table 1. Electrochemical performance data of the materials obtained in Examples 1-5 and Comparative Examples 1-3 of this invention.

[0066] (1) The experimental results of the batteries assembled in Examples 1-3 and Comparative Example 1 are shown in Table 1 and Figure 10 and Figure 11 As shown: In Example 1, the local W-doped 50W-20 material has a first-cycle discharge specific capacity (0.1C = 13 mA / g) in the voltage range of 2.0 to 4.1V, which is comparable to that of the undoped regenerated material (50W-0) in Comparative Example 1. However, the initial coulombic efficiency (ICE) is increased from 84.8% for 50W-0 to 90.5%, indicating that local doping is beneficial in improving reversibility.

[0067] Furthermore, the advantages of directional doping are even more pronounced during long-term cycling. At 1C, 50W-0 retains only 65.5% of its capacity after 150 cycles, with the rapid capacity decay stemming from strain in the material structure and side reactions. In contrast, 50W-20 achieves a capacity retention of 76.5%, and its post-cycle capacity retention of 91.3 mAh / g is significantly better than 50W-0's 76.1 mAh / g.

[0068] Overall, the reversible discharge specific capacity remained comparable after W doping, and the first-week coulombic efficiency was improved compared to the undoped sample. Compared to the doped sample, the lower ICE and faster capacity decay of the 50W-0 material obtained in Comparative Example 1 demonstrate the effectiveness and necessity of the material upgrade. Considering the specific surface exposure, regeneration growth, and directional exposure of the heterogeneous region after waste material treatment, the solvent composition of 50W can better balance solvent diffusion and desodium strain.

[0069] (2) The electrochemical properties of the materials obtained in Example 4 and Comparative Examples 1-2 were measured, and the results are shown in Table 1 and 2. Figure 12 As shown.

[0070] Table 1 and Figure 12 The difference in electrochemical performance further demonstrates the superiority of localized directional doping. Since W readily leads to layered structure evolution, conventional doping significantly increases polarization, making it difficult to realize the material's reversible capacity. However, localized directional doping, by introducing the same molar amount of W, can maintain high reversibility. Especially during long cycles, the inert interface caused by conventional doping results in a cycling capacity of only ~80 mAh / g at 1C, lower than the control examples 4-5 in the same group, demonstrating the negative effect of the phase transition interface. Such low capacity renders capacity retention meaningless in subsequent cycles. Localized directional doping not only avoids this adverse transformation but also leverages the positive effects of W doping, resulting in significantly improved stability compared to the undoped sample.

[0071] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets, characterized in that... Includes the following steps: S1, the waste electrode sheet is immersed in an aqueous solvent to peel off the waste positive electrode material and continue to soak it for sodium removal strain treatment; then, after solid-liquid separation and drying, material A is obtained; S2, Immerse material A in a salt solution containing the target dopant element to obtain material B; S3, sodium salt is added to material B for sodium supplementation treatment to obtain mixed powder C; mixed powder C is sintered to obtain sodium-based cathode material.

2. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S1, the chemical formula of the waste cathode material is Na. x Ni y Mn z Me w O2 and Me are selected from at least one of Fe, Mg, Al, Cu, Co, Sn, Ti and Zn, wherein 0≤x≤1, 0≤y≤0.5, 0.3≤z≤1.0, 0≤w≤0.4, and y+z+w=1.

3. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S1, the water-based solvent includes water or a mixture of water and a small molecule polar organic reagent, wherein the small molecule polar organic reagent includes one or more of methanol, ethanol, propanol, acetone, urea, and dimethyl sulfoxide. When the water-based solvent is a mixture, the mixing volume ratio of water to small molecule polar organic reagent is 1:(0.01~3).

4. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S1, the soaking time for stripping the waste positive electrode material is 0-10 min, and the sodium removal strain treatment is performed under ultrasonic conditions for 10-60 min.

5. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S2, the salt solution containing the target dopant element includes at least one of Li, Cu, W, and Ca, and the salt includes sodium salt, chloride salt, acetate, or nitrate. The solvent is the same as the water-based solvent in step S1. The concentration of the salt solution containing the target dopant element shown is from 0.1 mmol / L to saturation concentration.

6. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, Step S2 specifically includes: immersing material A in a salt solution containing the target dopant element, first sonicating for 10-60 minutes, then soaking for 5-24 hours to obtain material B.

7. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S3, the sodium salt includes at least one of Na2CO3, NaOH, NaNO3, and Na2O.

8. The method for locally controlling the regeneration of sodium-based cathode materials based on waste electrode sheets according to claim 1, characterized in that, In step S3, the sintering temperature is 600–1200°C, and the sintering time is 1–20 h.

9. The sodium-based cathode material regenerated by the method according to any one of claims 1-8.

10. The application of the sodium-based cathode material as described in claim 9 in the preparation of sodium-ion batteries.